Involvement of nitrate reductase in auxin-induced NO synthesis - Kolbert, Zsuzsanna (Landes Bioscience, 2008)
It is well known for a long time, that nitric oxide (NO) functions in variable physiological and developmental processes in plants, however the source of this signaling molecule in the diverse plant responses is very obscure.1 Although existance of nitric oxide sythase (NOS) in plants is still questionable, LNMMA (N(G)-monomethyl-L-arginine)-sensitive NO generation was observed in different plant species.2,3 In addition, nitrate reductase (NR) is confirmed to have a major role as source of NO.4,5 This multifaced molecule acts also in auxin-induced lateral root (LR) formation, since exogenous auxin enhanced NO levels in regions of Arabidopsis LR initiatives. Our results pointed out the involvement of nitrate reductase enzyme in auxin-induced NO formation. In this addendum, we speculate on auxin-induced NO production in lateral root primordial formation.